Structural modification of Naproxen; physicochemical, spectral, medicinal, and pharmacological evaluation - Md Omor Farque; Rahat Moinul Islam; Md Ferdous Rahman Joni; Mimona Akter; Shilpy Akter; Mohammad Didarul Islam; MD Jubaer Bin Salim; Ahamed Abdul Aziz; Emranul Kabir; Monir Uzzaman (Informatics in Medicine Unlocked)
Naproxen (Nap), a widely used nonsteroidal anti-inflammatory drug (NSAID), effectively reduces inflammation, pain, and fever by inhibiting cyclooxygenase enzymes (i.e., COX-1 and COX-2). However, its therapeutic use is often limited by significant adverse effects, including gastrointestinal hemorrhage, nephrotoxicity, hepatotoxicity, hematuria, and aphthous ulcers. In this study, we aimed to enhance both the efficacy and safety profile of Nap by making targeted structural modifications to the parent drug. Specifically, selected functional groups (i.e., CH3, OCH3, CF3, OCF3, NH2, CH2NH2, NHCONH2 and NHCOCH3) were introduced into the naphthalene nucleus. The geometry of the modified compounds was optimized via DFT with the B3LYP functional and 6-31+G (d, p) basis set, facilitating physicochemical and spectral analysis. Molecular docking studies were conducted against the human Prostaglandin G/H synthase 2 (5F19) and Mus musculus Prostaglandin-endoperoxide synthase 2 (3NT1), and these candidates were subjected to MD simulation. ADMET and PASS analyses were performed to evaluate the medicinal efficacy and toxicological profiles of the derivatives. Our findings identified several promising candidates with enhanced therapeutic benefits and reduced toxicity compared with the parent Nap. Docking analysis revealed that analogs exhibited stronger binding affinities compared to Nap and selectivity towards COX-2. These candidates demonstrated stability over a 100 ns MD simulation, exhibiting significant hydrogen bonding. Compared with the parent drug, most of these analogs displayed reduced hepatotoxicity, nephrotoxicity, carcinogenicity, and gastrointestinal hemorrhage activity, as supported by pharmacokinetic calculations. This study demonstrated that improved chemical and medicinal properties lead to a reduction in side effects.